2009
DOI: 10.1007/s00246-009-9582-3
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Children with Exercise-Induced Idiopathic Ventricular Arrhythmias

Abstract: Ventricular arrhythmias (VAs) are common pediatric rhythm disorders requiring comprehensive laboratory evaluation. Although usually idiopathic, implying a benign character and favorable prognosis, the initial clinical approach is still not established in all cases. Considering their prognostic significance, exercise-induced (precipitated or aggravated) VAs usually require additional diagnostics, treatment, and follow-up. A number of reports have presented experimental and clinical evidence that increased sympa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In many conditions, the balance between the sympathetic and parasympathetic systems is affected, and cardiac autonomic function disorders appear [28, 29]. Abnormalities on HRV as a marker of cardiac autonomic control are presumed to be risk factors for arrhythmia, and it has been shown that they can be used as reliable noninvasive markers of the presence of an underlying disease [3033]. In our study, HRV abnormalities were clearly shown in children with TCA intoxication during the first 24 hours of their admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many conditions, the balance between the sympathetic and parasympathetic systems is affected, and cardiac autonomic function disorders appear [28, 29]. Abnormalities on HRV as a marker of cardiac autonomic control are presumed to be risk factors for arrhythmia, and it has been shown that they can be used as reliable noninvasive markers of the presence of an underlying disease [3033]. In our study, HRV abnormalities were clearly shown in children with TCA intoxication during the first 24 hours of their admission.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased time-domain parameters, particularly SDNN, gave an idea about the association between the HRV results and ECG findings. Bjelakovic et al [33] found a marked decrease in the SDNN and SDANN levels in adults with exercise-induced ventricular arrhythmia, and they suggested that this decrease might be related to the direct effect of the sympathetic system on myocardial electrical activity. Changes in the RMSDD and pNN50 components also indicated that the autonomic system was affected by TCA poisoning via the vagus nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of neurocardiological disorders by Goldstein [1] is as follows: 1) Sympathetic disorders -diseases in which activation of the catecholamine system worsens an independent pathological state (coronary artery disease, arrhythmias as long QT syndrome, sudden death, heart failure (HF)) as well as diseases in which abnormal catecholaminergic function is etiologic (sympathetic neurocirculatory failure, hypertension, cardiac necrosis and cardiomyopathy), and 2) Vagally mediated disorders -both neurally mediated syncope (vasovagal syncope, carotid sinus hypersensitivity) and vagally mediated atrial fibrillation. Neural regulation of the CV system can be studied by using different techniques [2][3][4][5][6][7][8]. G protein related kinases (GRKs) exist in 7 isoforms -GRK 1-7.…”
Section: Neurocardiovascular Pathophysiology: Sympathetic Versus Vagamentioning
confidence: 99%
“…Heart rate variability (HRV) has been shown to be a marker of autonomic nervous system regulation of the heart. Changes in HRV are also associated with arrhythmias such as supraventricular and ventricular arrhythmias [ 8 , 9 ]. Specifically, in studies by Bergfeldt et al and Sosnowski et al, HRV was described as significantly higher in adult patients with SND than in controls [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%